Measurement of Serum Trace Elements (Zinc, Copper, Magnesium and Iron) Concentrations in Pediatric Patients with Otitis Media with Effusion in Iraq - K. Fakree, Najwan (Iraqi Journal of Pharmaceutical Sciences, 2017)
Otitis media with effusion (OME) is a common disease especially among young children (before school age) and it is one of the common causes of acquired hearing loss in childhood. Pediatric patients with OME are usually undernourished. The purpose of this study is to determine whether the serum levels of trace elements (zinc, copper, magnesium, iron) have a role in the development of OME in children. This study carried out on 55 children and subdivided them into two groups. Group 1 (patient group) consist of 30 children suffering from OME and group 2 (control group) included 25 apparently healthy children. Serum levels of zinc, copper, magnesium and iron were measured for both groups. Comparison the results between the two groups showed that group 1(patients) had significantly lower serum zinc, copper, and iron levels than group2 (P <0.05). Meanwhile the differences between the two groups in terms of serum values of magnesium were not statistically significant (p>0.05). This study postulated that serum levels of zinc, copper, and iron may have a role in the development of OME in children. While, serum magnesium may not have effect on the development of OME in children. Keyword: Pediatrics, Otitis media, Trace elements.